2011
DOI: 10.4061/2011/537101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Transcendental Meditation Program on Substance Use among University Students

Abstract: A randomized wait-list controlled trial (N = 295 university students) of the effects of the Transcendental Meditation program was conducted in an urban setting. Substance use was assessed by self-report at baseline and 3 months later. For smoking and illicit drug use, there were no significant differences between conditions. For alcohol use, sex X intervention condition interactions were significant; TM instruction lowered drinking rates among male but not female students. TM instruction could play a valuable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…A meta‐analysis of 4 randomized, controlled trials of mindfulness training involving a total of 474 patients found that it was more effective than group counseling, with 25% of mindfulness training participants remaining abstinent from smoking for >4 months, compared with 14% of those receiving more‐traditional cessation instruction . One study of Transcendental Meditation in 295 college students found no significant reduction in cigarette smoking at 3‐month follow‐up between those randomized to Transcendental Meditation and those in a wait‐list control group …”
Section: Effects Of Meditation On Smoking and Tobacco Usementioning
confidence: 99%
“…A meta‐analysis of 4 randomized, controlled trials of mindfulness training involving a total of 474 patients found that it was more effective than group counseling, with 25% of mindfulness training participants remaining abstinent from smoking for >4 months, compared with 14% of those receiving more‐traditional cessation instruction . One study of Transcendental Meditation in 295 college students found no significant reduction in cigarette smoking at 3‐month follow‐up between those randomized to Transcendental Meditation and those in a wait‐list control group …”
Section: Effects Of Meditation On Smoking and Tobacco Usementioning
confidence: 99%
“…Qualitative papers and survey reports were excluded, as well as those applying cross-sectional designs, or presenting observational data (Rogojanski et al, 2011b; Vidrine et al, 2009). We excluded articles in which smoking behavior or a predictor was not a primary inclusion criteria or outcome (Haaga et al, 2011). We considered a broad definition for smoking behavior, did not add study design to our inclusion/exclusion criteria, and did not limit the type or duration of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The current findings indicate that skills use was significantly improved and emotional dysregulation and emotional distress significantly reduced at the end of treatment in participants with a dual diagnosis. Mindfulness meditation skills have been consistently found to reduce substance misuse as a stand-alone treatment [24, 25]. Patients with BPD and SUD often experience increases in impulsivity.…”
Section: Discussionmentioning
confidence: 99%